A Level Set Immersed Boundary Method for Water Entry and Exit (Communications in Computational Physics, 2010)
The interaction between free surface flow and structure is investigated usinga new level set immersed boundary method. The incorporation of an improvedimmersed boundary method with a free surface capture scheme implemented in aNavier-Stokes solver allows the interaction between fluid flow with free surface andmoving body/bodies of almost arbitrary shape to be modelled. A new algorithm isproposed to locate exact forcing points near solid boundaries, which provides an accuratenumerical solution. The discretized linear system of the Poisson pressure equationis solved using the Generalized Minimum Residual (GMRES) method with incompleteLU preconditioning. Uniform flow past a cylinder at Reynolds number Re=100is modelled using the present model and results agree well with the experiment andnumerical data in the literature. Water exit and entry of a cylinder at the prescribedvelocity is also investigated. The predicted slamming coefficient is in good agreementwith experimental data and previous numerical simulations using a ComFlow model.The vertical slamming force and pressure distribution for the free falling wedge is alsostudied by the present model and comparisons with available theoretical solutions andexperimental data are made.